Promoting Equity and Assuring Teaching and Learning Quality: Magisterial Lectures in a Philippine University during the COVID-19 Pandemic - Rodrigo, Ma. Mercedes T. (Archīum Ateneo, 2022)
When the COVID-19 pandemic forced universities to shift to online learning, one of the challenges to faculty and administrators was to provide students with high-quality, curriculum-based learning materials that could be accessed despite students’ variable levels of Internet access. Part of the Ateneo de Manila University’s response to this challenge is the production of the Magisterial Lectures, an Open Educational Resource (OER) series of video lectures by some of the University’s most respected faculty members. The goals of this paper are to describe how the production of the lectures was guided by the principles of quality and equity; to discuss the use and reach of the lectures based on YouTube analytics and a survey of Ateneo students and teachers; and to measure the impact of the lectures on students’ learning experience. We enact quality in terms of curricular alignment and high production value. Equity was achieved by making the resource available publicly, free of charge. We found that the videos reached over 350,000 viewers in 37 countries. A survey of Ateneo students and teachers, the primary beneficiaries, shows that these materials were effective educational tools. Their effectiveness is attributable to the grounding of the production in quality and equity; the teachers’ careful integration of the recordings in their lessons; and the students’ engagement with the lectures following their own learning preferences and strategies.